RELATIONSHIP BETWEEN SELF-EFFICACY AND FEAR OF CANCER RECURRENCE IN CERVIX CANCER PATIENTS - Isran, Isran; Nuraini, Tuti; Afiyanti, Yati; Gayatri, Dewi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Fear of cancer recurrence (FCR) makes cancer patients physically and psychologically disturbed. FCR is caused by cancer patients' lack of ability or competence to exercise self-control (self-efficacy) while undergoing cancer treatment. This study aims to determine the relationship between self-efficacy and fear of recurrence in cervix cancer patients. The method used was cross-sectional, and it was carried out on 169 cervix cancer patients using the CBI (Cancer Behaviour Inventory) instrument to measure self-efficacy and the FCRI (Fear of Cancer Recurrence) instrument to measure fear of recurrence. The results showed that low self-efficacy 90 patients (52,3%) and high fear of cancer recurrence 89 patients (55%). The domain of coping with medication and side effects had the lowest Self-efficacy with 96 patients (56.8%) and the domain of functional impairment was the highest FCR domain with 84 patients (49.7%). However, that a significant relationship between self-efficacy and FCR in cervix cancer patients (p=0,012) with an OR 2,290. Self-efficacy is needed by cancer patients to overcome their fear of cancer recurrence. Therefore, help from health workers is needed to increase the self-efficacy of cancer patients.